TRANSFORMATION OF PUBLIC LEADERSHIP IN INDONESIAN INDUSTRIAL REGIONS IN THE LAST TWO DECADES - Af Sigit Rochadi (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
This article aims to explain the transformation of public leadership in the city of Batam. The research method used is semi-qualitative (quasy qualitative) and the results show that as an industrial society, charismatic leadership still takes place in the city of Batam. This type of leadership is mainly found in associations with the main basis of ethnic and tribal ties. Charismatic leadership is maintained through the preservation of the culture of origin in the city of Batam and events involving the heads of the ethnic origin areas. Transactional and transformational leadership does not work due to the dominance of the bureaucracy which is subject to the direction of the mayor. Even though each department has a work program and vision and mission, they are not a guide for leaders in moving the organization. The work program was defeated by the 'mayor's directive'. This happened because of the high dependence of service heads on the mayor. Bureaucratic domination supports the blunting of transformational leadership. The mayor who is directly elected by the people is a central figure in Batam so that the direction of change and resource mobilization can only come from the mayor. For this reason, continuous bureaucratic reform with transparent financial accountability is needed in order to restore transactional leadership.